Characteristic Board Of Directors And Investment Opportunity Set On Firm Value - Tyasha Ayu Melynda Sari; Halimatus Sa’diyah (SUSTAINABLE JURNAL AKUNTANSI, 2021)
The purpose of this study was to examine the effect of the characteristics of the directors and the Investment Opportunity Set (IOS) on firm value. The characteristics of the directors consist of age and gender. The sample used in this study is the Property, Real Estate, and Building Construction sectors listed on the Indonesia Stock Exchange (IDX) since the 2014-2018 period with purposive sampling method. The valid sample in this study is 218 observations for the CEO Age proxy, 219 observations for CEO Gender, and 220 observations for the Investment Opportunity Set. The data analysis technique used in this study used multiple linear regression analysis. Hypothesis testing is done by t-statistical test, F-statistical test, and the coefficient of determination (R2) test. The results showed that the age of the directors and the gender of the directors had no significant effect on firm value, while the Investment Opportunity Set (IOS) had a significant effect on firm value.